Characteristics of Sustainability Factors of Business Models in Community-Based Waste Management in Purwokerto City - Rusliati, Ellen; Mulyaningrum, Mulyaningrum; Mujibah, Mujibah; Yuwono, Wisnu; Jumbri, Isma Addi (Universitas Mercu Buana, 2025)
Objectives: This study aims to analyze the sustainability of the community-based waste management (CBWM) business model in Purwokerto City, with a focus on aspects of funding sources and financing mechanisms.Methodology: Through case studies, this study examines the sustainability of business models that can be applied in Purwokerto City. Data were collected through in-depth interviews with actors, direct observation, and documentation studies. Data analysis was carried out qualitatively to identify the sources of funding used, the financing mechanisms applied, and the factors that influence the sustainability of the business model.Finding: The study results show that several factors, including the availability of sustainable funding sources, effective financing mechanisms, and support from the government and the community, influence the sustainability of the CBWM business model in Purwokerto City. Conclusion: This study concludes that the CBWM business model has the potential to be a sustainable solution to overcome waste problems in Purwokerto City. However, further efforts are needed to improve the sustainability of this business model, such as diversifying funding sources, developing value-added recycled products, and increasing community capacity in managing waste.